Healthy Food Intake Index (HFII) - Validity and reproducibility in a gestational-diabetes-risk population - Jelena Meinilä; Anita Valkama; Saila B. Koivusalo; Beata Stach-Lempinen; Jaana Lindström; Hannu Kautiainen; Johan G. Eriksson; Maijaliisa Erkkola (BMC, 2016)
Abstract Background The aim was to develop and validate a food-based diet quality index for measuring adherence to the Nordic Nutrition Recommendations (NNR) in a pregnant population with high risk of gestational diabetes (GDM). Methods This study is a part of the Finnish Gestational Diabetes Prevention Study (RADIEL), a lifestyle intervention conducted between 2008 and 2014. The 443 pregnant participants (61 % of those invited), were either obese or had a history of GDM. Food frequency questionnaires collected at 1st trimester served for composing the HFII; a sum of 11 food groups (available score range 0-17) with higher scores reflecting higher adherence to the NNR. Results The average HFII of the participants was 10.2 (SD 2.8, range 2-17). Factor analysis for the HFII component matrix revealed three factors that explained most of the distribution (59 %) of the HFII. As an evidence of the component relevance 9 out of 11 of the HFII components independently contributed to the total score (item-rest correlation coefficients <0.31). Saturated fatty acids, monounsaturated fatty acids, polyunsaturated fatty acids, sucrose, and fiber intakes (among other nutrients) showed linearity across the HFII categories (P ≤ 0.030 for all nutrients tested); the higher the HFII, the closer the nutrient intake to the recommended intake level. Educational attainment (P = 0.0045), BMI (P = 0.0098), smoking (P = 0.007), and leisure time physical exercise (P = 0.038) showed linearity across the HFII categories. Intra-class correlation coefficient for the HFII was 0.85 (CI 0.79, 0.90). Conclusions The HFII components reflect the food guidelines of the NNR, intakes of relevant nutrients, and characteristics known to vary with diet quality. It largely ignores energy intake, its components have independent contribution to the HFII, and it exhibits reproducibility. The main shortcomings are absence of red and processed meat component, and the validation in a selected study population. It is suitable for ranking participants according to the adherence to the NNR in pregnant women at high risk of GDM.